TRACK YOURSELF AND SHARE WITH US. DIGITAL SELF-TRACKING AS A SOCIAL PRACTICE. - Kneidinger-Müller, Bernadette (AoIR Selected Papers of Internet Research, 2016)
Mobile and Wearable devices makes self-tracking as a practice of systematically recording information about one´s life easier than ever before. Self-tracking confirms the cultural expectations of the importance of self-awareness, reflection and responsibility and gives the users tools for managing themselves and improving their lives. Besides the automatization of collection and data processing especially the manifold ways of sharing individual life data forms the innovative character of modern self-tracking applications. People can share their individual measurements with other users on social media, blogs or in other forms of online or offline communities. Therefore, self-tracking may not be analyzed as an individual practice but have to be seen as a profound social and communicative practice. Despite a body of literature is beginning to emerge that addresses the social, cultural and political dimensions of self-tracking, only a few studies analyze systematically motivational and social factors for self-tracking. This research gap should be filled with findings from a two-step qualitative study: Users of self-tracking applications report their self-tracking behavior in a diary and are interviewed about their usage experiences, motives and sharing behavior of self-tracking data. Based on the diary and interview data the presentation intends to show why self-tracking can be seen as an expression of how the “rules” of the internet can change self-experiences and the way how personal data is handled.